Balance of confidentiality and tax transparency in legal regulation of automatic exchange of financial account information in the United States - G. P. Tolstopyatenko; S. S. Ageev (Правоприменение)
The subject of research, relevance. Exchange of information is an important measure of administrative cooperation between and among tax authorities aimed at the fight with tax evasion. Tax evasion is a problem that has gone beyond national borders, thus individual states can’t cope with it alone. In the light of this problem tax authorities develop new forms of administrative cooperation such as automatic exchange of information. While developing new forms, states should remember about the balance of private and public interest. In the context of automatic exchange of information this problem looks like a problem of finding a balance between confidentiality and tax transparency.The purpose. The article discusses the problem of finding a balance between confidentiality and tax transparency on the example of the United States. The choice of the United States may be explained by its national approach to such a balance that differs from the approach of other states that have implemented the Common Reporting Standard and Mandatory Disclosure Rules.The aim of the article is to show what peculiarities in national and international regulation in the United States influence their unique approach and what is the effect of this approach on the global system of automatic exchange of information and the rights of the US taxpayers.The methodological basis. The following scientific methods were used: comparative-legal, formal-juridical and historic-legal. The research was conducted in compliance with the principles of independence and verification of the results.The main results, scope of application. The conclusion of this article is that the balance of private and public interest in the context of automatic exchange of information is reached by the United States through confidentiality provisions exclusively. They use their national state legislation on beneficial ownership and the lack of reciprocity in intergovernmental agreements implementing FATCA to attract foreign investors (non-resident aliens) wishing to avoid reporting under the Common Reporting Standard. Meanwhile, the United States acquire full information on the financial accounts of their citizens and resident aliens who are beneficial owners of such accounts held in foreign financial institutions. Such a state of affairs is dangerous for the effectiveness of the global system of automatic exchange of information. Moreover, it impairs the rights of Accidental Americans who permanently reside in foreign states and have no connection with the United States except for their citizenship but still have reporting obligations before the US Internal Revenue Service.Conclusions. Automatic exchange of information should be developed in compliance with the principle of balance between tax transparency and confidentiality. States should follow one and the same approach to providing such a balance. At the same time the taxpayers’ rights, in particular the rights of Accidental Americans, should be protected and they can’t be outweighed by the need of administrative cooperation between or among tax authorities.